Pengaruh Satisfaction, Trust, Commitment Terhadap Word of Mouth Pada Rumah Makan Sambalado di Kota Padang - Zulherwan Zulherwan; Abror Abror (Universitas Negeri Padang, 2019)
This study aims to analyze: (1) The effect of satisfaction on word of mouth at sambalado restaurant in padang city (2) The effect of trust on word of mouth at sambalado restaurant in padang city (3) The effect of commitment on word of mouth at sambalado restaurant in padang city. this type of research is causative research; this research was conducted in the city of padang. the population in this study were consumers who had visited sambalado padang restaurant. the sample used was 170 people using purposive sampling technique. the type of data in this study are primary and secondary data. data analysis using the smartpls version 3.0 program. the results of this study indicate that: (1) satisfaction has a significant effect on trust in sambalado restaurant in padang city, (2) satisfaction has a significant effect on word of mouth at sambalado restaurant in padang city, (3) satisfaction has a significant effect on commitment to sambalado restaurant in padang city, (4) trust has asignificant commitment to sambalado restaurant in padang city, (5) trust does not significantly influence word of mouth at sambalado restaurant in padang city, (6) commitment has a significant effect on word of mouth at sambalado restaurant in padang city. Keywords: Satisfaction, Trust, Commitment, Word of Mouth